2009
DOI: 10.1111/j.1469-0691.2009.02752.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of steroids during sepsis depend on dose and severity of illness: an updated meta-analysis

Abstract: A previous meta-analysis determined that the effects of steroids during sepsis were dose-dependent; since then, additional trials have been published. The current analysis updates our previous analysis examining the effects of steroids during sepsis. A literature search from 2004 to 2008 identified seven randomized controlled trials in adult patients; these were added to 14 previously identified trials. The effects of steroids on mortality were highly variable among the 21 trials (p <0.001, I2 = 60%). In trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 44 publications
4
90
1
3
Order By: Relevance
“…1,7 More data support the role of corticosteroids in reversing shock and decreasing mortality mainly in patients with sepsis-induced hypotension refractory to fluid replacement and vasopressor therapy. 25 The 2012 Surviving Sepsis Campaign recommended administration of intravenous hydrocortisone alone at a dose of 200 mg/day as a treatment of adult septic shock patients only if adequate fluid resuscitation and vasopressor therapy are not able to restore hemodynamic stability. Another controversy is related to the use of ACTH stimulation test to identify the subset of adults with septic shock who should receive hydrocortisone.…”
mentioning
confidence: 99%
“…1,7 More data support the role of corticosteroids in reversing shock and decreasing mortality mainly in patients with sepsis-induced hypotension refractory to fluid replacement and vasopressor therapy. 25 The 2012 Surviving Sepsis Campaign recommended administration of intravenous hydrocortisone alone at a dose of 200 mg/day as a treatment of adult septic shock patients only if adequate fluid resuscitation and vasopressor therapy are not able to restore hemodynamic stability. Another controversy is related to the use of ACTH stimulation test to identify the subset of adults with septic shock who should receive hydrocortisone.…”
mentioning
confidence: 99%
“…A significant inverse-linear relationship between disease severity and an OR of mortality was found in the analysis, indicating that in less severely ill patients, steroids may be harmful. 38 Another large meta-analysis in the same year found that when a group of RCTs published between 1998 and 2009 evaluating long duration of low-dose steroid therapy, were assessed in isolation, an improved mortality was observed in the treatment group compared to the control group (37.5% vs 44.1%) (RR 0.84; 95%CI 0.72 to 0.97; P=0.02). 39 There was also evidence of increased rates of hyperglycemia and hypernatremia with corticosteroid treatment in this study.…”
Section: Systematic Review and Meta-analyses Conducted On The Use Of mentioning
confidence: 99%
“…Possible contributing factors are that CORTICUS enrolled patients later (up to 72 hours in septic shock), with lower disease severity, as opposed to targeting patients early in their disease (3-8 h) who are poorly responsive to vasopressors, which was the Annane protocol. An updated meta-analysis combining all trials published after 1997 concluded that low-dose corticosteroids consistently improves shock reversal, but decreases mortality only patients with more severe septic shock who are at the highest risk of death [29]. Low-dose steroids appear to increase mortality or have no effect in less severely ill patients with sepsis.…”
Section: The Evidence For Corticosteroid Supplementation In Severe Sementioning
confidence: 99%